A STUDY ON THE ABILITY OF THE TENTH GRADE AT SMA N I TAMBANG IN UNDERSTANDING DESCRIPTIVE TEXT - Marwa Marwa (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2015)
In SMA N 1 TAMBANG, the researcher found Based on the result of observation thefact shows that most of the students have low ability in descriptive text, especially at the tenthgrade students. It perhaps, caused by several factors such as, some students do not know genericof structure, some students do not really understand about information of given paragraphs, somestudents do not fully know the meaning of vocabulary, some students have problem in thebackground knowledge of the text given, and some students get bored they have to as look up adictionary in frequent. This research was conducted to know the students ability in understandingdescriptive text and what factor influence their ability. Survey design was method used in thisresearch. There was quantitative descriptive statistic. The result showed that the ability of the attenth grade SMA N 1 TAMBANG in understanding descriptive text. The average of mean scoreof the students’ ability in understanding descriptive text is 56.5. It could be identified that thestudents’ ability in understanding descriptive text is categorized into less. It is hoped that thefinding of the present study will be useful for the teaching of English, especially inunderstanding descriptive text.